Permodelan Produksi Kopi Indonesia dengan Menggunakan Seasonal Autoregressive Integrated Moving Average (SARIMA) - Hutomo Atman Maulana; Kasuma Wardany Harahap; Adriyansyah Adriyansyah; Rofiroh Rofiroh; Fuad Zainuddin (JURNAL SAINTIKA UNPAM, 2019)
This research used a method in modelling time series data in the form of seasonal data. The method used in this study is the Seasonal Autoregressive Integrated Moving Average (SARIMA). This method is applied to Indonesian coffee production data from January 2009 - December 2013 with the aim of obtaining a model that will be used to predict the amount of coffee production in January 2014 - December 2014. The forecasting results from the next model will be compared with the original data. Data processing is done using EViews software. Based on the results of data processing, the best model for forecasting is obtained, SARIMA (2,1,0) (1,1,1)12